2016
DOI: 10.1007/s40891-016-0064-4
|View full text |Cite
|
Sign up to set email alerts
|

Unconfined Compressive Strength of Compacted Disturbed Cement-Stabilized Soft Clay

Abstract: Pneumatic flow mixing method is a new land reclamation method, developed in Japan to meet the persistent lack of space. In this method dredged soft soil is mixed with a small amount of stabilizing material (such as cement) during transporting the soft soil in a pipe using compressed air to be used for land reclamation. In some cases, the soil/cement mixture is stored in temporary place for days and then transported and compacted at the required place. Basically, the cement chemical reaction starts immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This is in line with the general trends found in previous works [48,49], where an increase in the E 50 modulus was observed when the UCS increased. According to Ayeldeen et al [50], E 50 can be estimated for disturbed cement-stabilized soft clay as between 25 to 50 times UCS. Other authors increase this value to between 50 to 150 times [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the general trends found in previous works [48,49], where an increase in the E 50 modulus was observed when the UCS increased. According to Ayeldeen et al [50], E 50 can be estimated for disturbed cement-stabilized soft clay as between 25 to 50 times UCS. Other authors increase this value to between 50 to 150 times [51].…”
Section: Discussionmentioning
confidence: 99%
“…Ayeldeen et al [50] reported that undisturbed cement-stabilized clay, with higher ratios E 50 /UCS, up to 160, shown brittle behavior with a clear peak. Nevertheless, re-molded samples with lower ratios have shown a ductile strain-stress behavior without a clear peak.…”
Section: Discussionmentioning
confidence: 99%
“…For quarry fines stabilized with Ecolan and fly ash-based stabilizers (with activator), the coefficients are of 72 to 468 × UCS and of 35 to 179 × UCS respectively. The multiplier coefficients of Ecolan-stabilized quarry fines are higher than the typical coefficients of undisturbed cemented clays from 50 to 300 [37], while the fly ash-stabilized quarry fines have similar coefficients to undisturbed cemented clays.…”
Section: Characterization Of Stabilized Quarry Fines As Constructimentioning
confidence: 99%
“…This particular test has also been frequently used in many experimental programmes reported in the literature (e.g. Consoli et al 2012;Kaniraj and Havanagi, 1999;Ayeldeen et al 2016;Yi et al 2014) in order to verify the effectiveness of the soil stabilisation with cement, or to explore the relative importance of the factors controlling the stiffness of the cemented soils.…”
Section: Introductionmentioning
confidence: 99%